Vascularization of Leaves and Stem of the Species Galium Aparine L. - Gharb, Lamiaa; Al-Musawi, Ali (Iraqi Journal of Science, 2024)
The research is an anatomical study for the stem and leaves of Galium aparineL.The nodal anatomy was carefully investigated ,by the cross sections at the nodeprovide that what was called "cyclic arrangement" of leaves is in fact includes justtwo opposite leaves which take their vascularization from the stele by two leaftraces.The rest four leaf- like appendages on the node are stipules ,and take theirvascularization from the vascular ring which bond the two opposite leaves,andrefered for some morphological and anatomical characters of the plant species in thiswork.